al-Kitābah al-abjadīyah fī Miṣr al-qadīmah : awwal ihtidāʼ li-mabdāʼ al-abjadīyah - ʻAbd Allāh, ʻAbd al-Qādir Maḥmūd, 1937- (ʻAmādat Shuʾūn al-Maktabāt, Jāmiʻat al-Malik Saʻūd, 1995)
On the development of alphabetic writing in ancient Egypt.